Heterogeneity in the marginal propensity to consume: Evidence from Covid-19 stimulus payments - Ezra Karger; Aastha Rajan (Federal Reserve Bank of Chicago, 2020)
We identify 16,016 recipients of Covid-19 Economic Impact Payments in anonymized transaction-level debit card data from Facteus. We use an event study framework to show that in the two weeks following a sudden 1,200 payment from the IRS, consumers immediately increased spending by an average of 577, implying a marginal propensity to consume (MPC) of 48%. Consumer spending falls back to normal levels after two weeks. Stimulus recipients who live paycheck-to-paycheck spend 68% of the stimulus payment immediately, while recipients who save much of their monthly income spend 23% of the stimulus payment immediately. Consumer age and location are only marginally correlated with individual MPCs after controlling for each individual's pre-pandemic propensity to save. We use the 2018 American Community Survey to re-weight our data to match the U.S. population. Ignoring equilibrium effects and assuming a constant MPC for each person, we estimate that the CARES Act's 296 billion of payments to individuals will increase consumer spending by 138 billion (47% of total outlays). A stimulus bill of the same size targeted at individuals with the highest MPCs would have instead increased consumer spending by 201 billion (68% of total outlays).
Keywords: D04; D12; E21; 330; Covid-19; stimulus payments; high-frequency data; marginal propensity to consume